Micro Injection Moulding Process Parameter Tuning - Packianather, Michael; Griffiths, Christian; Kadir, Wan (Procedia CIRP, 2015)
This paper focuses on tuning the micro injection moulding process parameters. In this study four process parameters namely, barrel temperature, mould temperature, holding pressure and injection speed were considered. In order to capture their behaviour a L16 Orthogonal Array with two levels for each parameter was employed to produce the design of a 15mm x 20mm x 1mm microfluidic platform using Cyclic Olefin Copolymer (COC), a common polymer. The demoulding force was measured during the micro injection moulding process. The sixteen trials were repeated ten times to incorporate process variation, systematic and random noise in the experimental procedure. The results were analysed using Taguchi method to identify the influence of the process parameters upon the demoulding force and their sensitivity to noise. In addition, the results also indicated either the presence or absence of the two level interactions between these process parameters. This study has contributed to understanding the characteristics of these process parameters in terms of their main effects, interactions and sensitivity to noise and to tune them for their optimal performance.